Sharing Economy, Sharing Responsibility? Corporate Social Responsibility in the Digital Age - Etter, Michael (Journal of business ethics, 2019)
The sharing economy has transformed economic transactions, created new organizational forms, and contributed to changes in consumer culture. Started as a movement with promises of a more sustainable, democratic, and inclusive economy, the sharing economy, and its impact on issues such as privacy, discrimination, worker rights, and regulation, is now the subject of heated debate. Many of these issues root in the changes that digital technologies have brought and the unresolved moral and ethical questions emerging therefrom. This special issue contributes to this ongoing debate with five articles that develop theoretical frameworks and conduct empirical investigations, providing fine-grained analyses of urgent issues in the sharing economy. In this article, we highlight these and other issues that we believe deserve further attention from business ethics scholarship.